2019
DOI: 10.1038/s41598-019-54997-z
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Tracing microplastics in aquatic environments based on sediment analogies

Abstract: Representative replicates (n = 3) were available for station S2 and S10 amounting to 78 ± 10 g −1 DW and 379 ± 28 g −1 DW, respectively. " now reads "Representative replicates (n = 3) were available for station S2 and S10 amounting to 78 ± 10 kg −1 DW and 379 ± 28 kg −1 DW, respectively. " In the legend for Figure 2 "The black line indicates the transition from LD to HD polymers determined by the density of water (~1 g m −3). " now reads "The black line indicates the transition from LD to HD polymers determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Sediments, both freshwater and marine, act as sinks for microplastics (MP) whether due to rapid sinking of high-density plastic particles , settling caused by biofouling , or incorporation in sinking organic aggregates, e.g., marine snow Zhao et al, 2018). Settled MP particles may subsequently be resuspended and further transported with water currents to settle in calmer areas with finer sediments far away from their source (Enders et al, 2019). Because sediments in calm areas accumulate and sequester deposited MP, they provide a temporal record of MP input to the aquatic environments and thus also constitute a relevant matrix for monitoring.…”
Section: Status Of Understanding For a Representative Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Sediments, both freshwater and marine, act as sinks for microplastics (MP) whether due to rapid sinking of high-density plastic particles , settling caused by biofouling , or incorporation in sinking organic aggregates, e.g., marine snow Zhao et al, 2018). Settled MP particles may subsequently be resuspended and further transported with water currents to settle in calmer areas with finer sediments far away from their source (Enders et al, 2019). Because sediments in calm areas accumulate and sequester deposited MP, they provide a temporal record of MP input to the aquatic environments and thus also constitute a relevant matrix for monitoring.…”
Section: Status Of Understanding For a Representative Samplementioning
confidence: 99%
“…Our knowledge regarding MP fate processes is still limited, which makes it difficult to pinpoint locations of MP accumulation. Some studies show correlations between MP and sediment grain size and/or organic matter content (Strand et al, 2013;Vianello et al, 2013;Enders et al, 2019;, whereas other studies find no such correlation (Alomar et al, 2016;Peng et al, 2017). In a largescale, meta-analysis, Erni-Cassola et al, 2019 showed a high general accumulation of MP in intertidal sediments.…”
Section: Current Levels In the Arcticmentioning
confidence: 99%